Subcutaneous Fat Necrosis of the Neonate with a Delayed Second Eruption. Issue 2 (29th January 2016) - Thomas, Justyn M.; Bhandari, Jasjit; Rytina, Ed; Gass, Julia K.; Williams, Rachel M.; Burrows, Nigel P.
Abstract: Subcutaneous fat necrosis (SCFN) of the neonate is a rare panniculitis of early life that occurs in association with gestational diabetes and preeclampsia, as well as perinatal asphyxia, hypothermia, and trauma. A characteristic feature of this condition is its self‐limiting and monophasic nature. We report a highly unusual case of delayed SCFN in a male neonate involving an anatomically discrete eruption, reminiscent of erythema nodosum, occurring many weeks after his original eruption had resolved.